Picture-based crop insurance: Using smartphone camera data for claims verification in India - Ceballos, Francisco; Gaur, Pushkar; Gupta, Monali; Kannan, Samyuktha; Kramer, Berber (International Initiative for Impact Evaluation, 2025)
This brief discusses the findings of an impact evaluation of a picture-based crop insurance scheme that uses smartphone camera data for claims verification in India. 3ie initially received funding for the Agricultural Insurance Evidence Program from UK aid through the Department for International Development (now known as FCDO). The program is now funded by the Bill & Melinda Gates Foundation.